Limb apraxia without aphasia from a left sided lesion in a right handed patient. Issue 8 (August 1991) - Selnes, O A; Pestronk, A; Hart, J; Gordon, B
Abstract : A right handed man had a massive left middle cerebral artery stroke. CT and MRI revealed extensive destruction of both anterior and posterior areas typically associated with language. There was, however, no aphasia, but instead a marked limb apraxia, dyscalculia, dense right visual neglect, and anosognosia. These uncommon dissociations and associations support the hypothesis that cerebral control of motor function of the limbs is not fundamentally related to the motor control involved in speech, and the notion that handedness is related to laterality of motor control, and only accidentally to laterality of language control.